Indian Agriculture Farm Acts: 2020 - Amar Shankar (International Journal of Modern Agriculture, 2021)
Agriculture is a state subject in India, and state-level Agriculture Produce Marketing Acts regulate agriculture marketing. The latter is in charge of establishing Agriculture Produce Marketing Committees (APMCs), which have become a point of contention in these Acts. In order to reform Indian agriculture, the central government introduced three bills, which became law after obtaining constitutional assent in the month of September 2020. The three of the bills implemented: (Promotion and Facilitation) The Farmerâ€™s Produce Trade & Commerce Bill, (Amendment) Essential Commodity Bill & (Empowerment and Protection) Farmersâ€™ Agreement on the Price Guarantee & Farm Service Bill, 2020. Farmers’ protests and marches, as well as political unrest, have erupted in reaction to the introduction of the three bills. The three acts’ aim is to reduce state control over the buying, selling, storage, and transporting of farm produce across the country, as well as to make it easier for private players to enter the market, which is currently hindered by entry barriers. Current study is based on the various Farm Acts implemented by the government and its advantages and disadvantages for the Indian agriculture and economy. The Indian Farm Acts, 2020 were likely to make an exposed market for inter & intra-state agriculture trade & take freedom for choice for farmer where the farmer & trader can appreciate the freedom for choice related to sale & purchase of farmer yield that enables remunerative values by viable interchange channel to promote efficient, transparent and barrier-free inter-state and intra-state agriculture marketing. Current study will aid the readers in gaining a better understand and spread awareness about the bills.